The effectiveness of combined approaches towards improving utilisation of adolescent sexual and reproductive health services in Kenya: a quasi-experimental evaluation - Lilian Mutea; Justinah Maluni; Mark Kabue; Vincent Were; Susan Ontiri; Kristien Michielsen; Peter Gichangi (Sexual and Reproductive Health Matters, 2023)
Adolescent sexual and reproductive health (ASRH) services are key to improving the health of adolescents. This study aimed to establish the effectiveness of an intervention that combined activities in health facilities and communities in Kenya to increase utilisation of ASRH services. A quasi-experimental evaluation design was used to assess the effectiveness of the intervention. Using a stratified cluster sampling approach, two cross-sectional household surveys targeting girls aged 15–19 were conducted at baseline (September 2019) and endline (December 2020) in intervention and comparison. We combined the difference-in-difference approach to analyse the net change in outcomes between intervention and comparison arms of the study at baseline and endline and coarsened exact matching for variables that were significantly different to address the imbalance. There were a total of 1011 participants in the intervention arm and 880 in the comparison arm. Descriptive results showed a net increase of 12.7% in intervention sites in the knowledge of misconceptions about sex, pregnancy, and contraception, compared to 10.4% in the control site. In the multivariate regression analysis, two outcomes remained significant: decreases in adolescents’ discomfort when seeking ASRH services because of either fear of parents (aPR = 0.58, 95% CI = 0.42–0.79, P = 0.001) or a lack of support from their partner (aPR = 0.25, 95% CI = 0.08–0.82, P = 0.023). The intervention combining a facility and community approach was not effective in increasing the use of ASRH information and services. Possible reasons for this are explored.